Intratympanic VII nerve schwannoma without facial paralysis: A rare cause of aural polyp - Araújo-Martins, José (2014)
Facial nerve schwannomas are the second most common type of benign neoplasia of the middle ear after paragangliomas. When their origin is intratympanic, signs and symptoms develop earlier. The most frequent complaints are facial paralysis and hypoacusis. We report the case of a patient with unilateral conductive hypoacusis, an aural polyp and imagiologic changes suggesting a middle ear schwannoma. The diagnosis was confirmed by pathology after full excision of the lesion through radical mastoidectomy. In the post-operative period, the hearing loss is unchanged and the patient has normal facial function (I/VI, House-Brackmann). The absence of facial paralysis is an uncommon presentation for these lesions and we have found only two cases reported with aural polyp and no facial paralysis. The full excision of these extensive lesions can be performed while maintaining the pre-operative hearing thresholds and facial function.